Efektivitas Terapi Tawa untuk Mengelola Stress: Sebuah Meta-Analisis - William, Kevin; Yudiarso, Ananta (Fakultas Psikologi Universitas YARSI, 2024)
Stress is a common issue faced by the Indonesian population, and laughter therapy is believed to be an effective intervention. However, findings from previous research have yielded inconsistent results regarding the effectiveness of laughter therapy. This study evaluates the effectiveness of laughter therapy as an intervention to reduce stress in the Indonesian population through Hedge's G meta-analysis, following the PRISMA 2020 guidelines. The analysis involved 347 participants from 9 previous studies. The results indicate that laughter therapy has a significant effect in reducing stress levels in individuals. Laughter therapy with 15 steps proved to be the most effective model. The implications of these findings are significant in understanding the role of laughter therapy as a potential strategy in addressing stress in the community. This study provides substantial empirical evidence for mental health practitioners and researchers to incorporate laughter therapy, particularly with proven effective approaches, as an integral part of comprehensive mental health efforts in Indonesia.